Marca d'água o ser e o existir do rural no espaço metropolitano de Goiânia - Oliveira, Ubiratan Francisco (2011)
This research work focuses on the process of Goiânia metropolization having as object of analysis the rural in the city. The way that Goiânia was projected in the design of "City-Garden" brought from Europe in the early 20th century, by Architect Planner Atilius Corrêa Lima, expresses well the city's relationship with the countryside. Goiânia, a planned city under the aegis of modernity, occupied originally by the territory's agrarian society, the rural tradition of Goias his subjects, culture, way of being and acting of country man from Brazilian Cerrado (?). The design of City-Garden sought rapprochement of the field with city, rural livelihoods and urban to justify the creation of a city full of signs of modernity, advancement and progress that would provide the order of "isolation" of Goiás in relation to urban industrial society of Southeast Brazil. Thus, Goiânia should, at the same time, expressing his strong relationship with the field, but also, paradoxically, denying the rural way of life which is subjecting the inhabitants of Goiás. Rural and urban shall be more than spatial dichotomies to become socioeconomic dichotomies, the place of the "backwardness and stagnation" should be replaced by the place of the "advancement" and of the economic and social progress. This conflict materializes the hegemony of industrial capitalism on the territory of Goias and Goiânia is the hallmark of this hegemony. The symbol of modernity which arrives at the Center-Western Brazil to open the doors to progress. However, the process of metropolization took place quickly and provided a "disconnect" between time, space and subject. With significant structural changes in the rural space that they entered subject to urban life time slow quick time, had as a consequence the emergence of a metropolis with its urban fabric of loaded free that express the existence of rural in the city. This Rural, manifested in the form, the structure and function of these spaces in the city having as an agent of incorporation the rural subject with his technique and strength that characterize as workers and rural workers in the social division of labour. The relationship of rural with Goiânia and Goiânia with the peculiar form of rural and that needs a watchful as a look needed to see a stamp watermark that sometimes needs of body contact and tact to be unveiled. We thus contribute to the debate over relations city-countryside, urban-rural and city-rural and urban-field seeking to understand the social phenomena of "new rural" and new "ruralidades" in contemporary society.